Evaluation of a cyberbullying prevention program in elementary schools: The role of self-esteem enhancement - Touloupis, Thanos; Athanasiades, Christina (Frontiers in Psychology, 2022)
Although elementary schools are considered a fertile ground for promoting positive behaviors among students (such as safe online practices), to date, almost no study has examined the effectiveness of a cyberbullying prevention program among elementary school students of typical and non-typical development. The present study evaluated the effectiveness of such a school-based European funded preventive program (TABBY, Threat Assessment of Bullying Behavior in Youth) among sixth graders with and without special educational needs (SEN). The study also examined the predictive role of self-esteem in students’ cyberbullying involvement. Overall, 240 students from randomly selected Greek schools completed a self-report questionnaire, which included a scale on cyberbullying and self-esteem. Following an experimental longitudinal research design, the intervention was applied to the experimental (N = 120) but not to the control group of students (N = 120). Each group consisted of both students with (N = 60) and without SEN (N = 60). The evaluation was based on the completion of the self-report questionnaire before (1st phase), immediately after (2nd phase), and 6 months after the intervention was completed (3rd phase) by trained general and special education teachers. According to the findings, students’ cyberbullying engagement (as bullies/victims) decreased significantly in the second and third phase, and especially for those with SEN. Additionally, self-esteem negatively predicted students’ involvement in cyberbullying (as bullies/victims) in all three phases. The findings partially support the appropriateness of interventions within the elementary school context in order to enhance self-esteem and promote a safe online culture among students of typical as well as atypical development.